EU public construction law - Vomáčka, Vojtěch, 1984- (Scientia est Potentia, 2025)
The monograph traces the degree of indirect harmonisation of spatial planning and planning permission in EU law and the scope of the relevant requirements. It focuses on the gradual development of EU law, the relationships, differences and synergies between the different conditions in order to provide a more comprehensive picture, and then concentrates on the most critical issues identified, namely the interpretation of the general concepts used in environmental legislation and the explanation of the content of the public participation requirements. It also examines the relationship between the Aarhus Convention and EU law, highlighting the fundamental guarantees of participation in decision-making and access to justice. Furthermore, the monograph analyses the requirements for planning and construction arising from so-called non-environmental EU policies. It focuses in particular on the development of cohesion policy and the urban agenda, maritime spatial planning, the development of the TEN-T and TEN-E networks, requirements for building materials, energy efficiency in buildings and the promotion of renewable energy.";EU public construction law"